Simulation of load driving series resonant inverter; 5th International Siberian Workshop and Tutorials on Electron Devices and Materials: EDM'2004, Erlagol, Altai, July 1-5, 2004 - Kozhemyak O. A. Olesya Anatolievna (2004, 2004)
Title screen